2020
DOI: 10.1159/000510336
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Cancer Genomics in State Health Agencies: Mapping Activities to an Implementation Science Outcome Framework

Abstract: Objective: To show how state health agencies can plan and evaluate activities to strengthen the evidence base for public health genomics, we mapped state cancer genomics activities to the Doyle et al. [Genet Med. 2018;20(9):995–1003] implementation science outcome framework. Methods: We identified state health agency activities addressing hereditary breast and ovarian cancer and Lynch syndrome by reviewing project narratives from Centers for Disease Control and Prevention Cancer Genomics Program funding recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 21 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Studies/reports were categorized according to the level of clinical health care addressed: the health care system (ie, strategic), an organization (ie, operational), or a team (ie, operational). Most commonly, studies targeted both organization and team levels (n = 11), [16][17][18][19][30][31][32][33][34][35][36] followed by the health care systems and organizations (n = 8). 15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5).…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
See 4 more Smart Citations
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Studies/reports were categorized according to the level of clinical health care addressed: the health care system (ie, strategic), an organization (ie, operational), or a team (ie, operational). Most commonly, studies targeted both organization and team levels (n = 11), [16][17][18][19][30][31][32][33][34][35][36] followed by the health care systems and organizations (n = 8). 15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5).…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
“…15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5). [16][17][18][19]30,[32][33][34][35][36][37] Most studies/reports identified were driven by government bodies (n = 13), [21][22][23][25][26][27][28][29]31,[38][39][40][41] with 10 of these as government reports rather than research studies. [21][22][23][25][26][27][28][29]40,41 Another 13 were conducted by independent academics.…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
See 3 more Smart Citations